The role of the blood–brain barrier in the development and treatment of migraine and other pain disorders - DosSantos, Marcos F.; Holanda-Afonso, Rosenilde C.; Lima, Rodrigo L.; DaSilva, Alexandre F.; Moura-Neto, Vivaldo (Frontiers in Cellular Neuroscience, 2014)
The function of the blood-brain barrier (BBB) related to chronic pain has been explored by its classical role in regulating the transcellular and paracellular transport, thus controlling the flow of drugs that act at the central nervous system, such as the opioid analgesics (e.g., morphine) and non-steroidal anti-inflammatory drugs (NSAIDs). Nonetheless, recent studies have raised the possibility that changes in the BBB permeability might be associated with chronic pain. For instance, changes in the relative amounts of occludin isoforms, resulting in significant increases in the BBB permeability, have been demonstrated after inflammatory hyperalgesia. Furthermore, inflammatory pain produces structural changes in the P-glycoprotein (P-gp), the major efflux transporter at the BBB. One possible explanation for these findings is the action of substances typically released at the site of peripheral injuries that could lead to changes in the brain endothelial permeability, including: substance P, calcitonin gene related peptide (CGRP) and IL- 1β. Interestingly, inflammatory pain also results in microglial activation, which potentiates the BBB damage. In fact, astrocytes and microglia play a critical role in maintaining the BBB integrity and the activation of those cells is considered a key mechanism underlying chronic pain. Despite the recent advances in the understanding of BBB function in pain development as well as its interference in the efficacy of analgesic drugs, there remain unknowns regarding the molecular mechanisms involved in this process. In this review, we explore the connection between the BBB as well as the blood-spinal cord barrier (BSCB) and blood-nerve barrier (BNB) and pain, focusing on cellular and molecular mechanisms of BBB permeabilization induced by inflammatory or neuropathic pain and migraine.